Relationships between adolescent students’ reading skills, historical content knowledge and historical reasoning ability - ter Beek, Marlies; Opdenakker, Marie-Christine; Deunk, Marjolein I.; Strijbos, Jan-Willem; Huijgen, Tim (History education research journal., 2022)
The ability to apply various reading skills is an important prerequisite to comprehend expository texts commonly found in history textbooks, but it is unclear which specific skills contribute to students’ historical content knowledge and historical reasoning abilities. This study used a digital learning environment (DLE) to measure and support lower secondary students’ subject-specific reading skills, and explored the relationships with students’ historical content knowledge and historical reasoning ability. Results showed that subject-specific reading skills, such as explaining historical events, correlated significantly with both historical content knowledge and historical reasoning ability, but not all skills were significant predictors. These findings indicate that to promote the advanced practice of historical reasoning, history teachers should pay attention to students’ reading comprehension skills.